2022
DOI: 10.1007/s13644-021-00465-y
|View full text |Cite
|
Sign up to set email alerts
|

Pastoral Ministry in Unsettled Times: A Qualitative Study of the Experiences of Clergy during the COVID-19 Pandemic

Abstract: Background COVID-19 and its associated restrictions around in-person gatherings have created unprecedented challenges for religious congregations and those who lead them. While several surveys have attempted to describe how pastors and congregations responded to COVID-19, these provide a relatively thin picture of how COVID-19 is impacting religious life. There is scant qualitative data describing the lived reality of religious leaders and communities during the pandemic. Purpose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 20 publications
2
39
0
2
Order By: Relevance
“…They also provided counseling when needed. These findings aligned closely with Johnston et al (2021) . These researchers used Swiler’s Framework to analyze their data.…”
Section: Discussionsupporting
confidence: 81%
“…They also provided counseling when needed. These findings aligned closely with Johnston et al (2021) . These researchers used Swiler’s Framework to analyze their data.…”
Section: Discussionsupporting
confidence: 81%
“…This literature suggests that congregations that are smaller, located in rural areas, are in a more liturgical tradition such as Catholicism, are predominantly Black, have older members, and have more lower income members will be less likely to have both the financial and technological infrastructure that could help mitigate the social and economic effects of the COVID-19 pandemic. Some early research on how religious leaders have responded to COVID-19 has already shown that responses and readiness to face the pandemic differed across religious tradition (Sulkowski and Ignatowski 2020) and rural/urban location (Village and Francis 2020;Johnston et al 2021), but there is still limited research conducted on a broadly representative sample documenting which congregations were more vulnerable to the effects of COVID-19 on the eve of the pandemic. In this article we examine the ways that these congregational characteristics intersect and overlap with one another to identify the congregations that appear to be most vulnerable in a time of social distancing and its associated financial challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Writing amid COVID, Tim Hutchings ( 2020 ) suggested three common reasons for online churches: “The desire to amplify, to connect, and to experiment” (61). Johnston et al ( 2021 ) note a lack of qualitative data on the lived reality of religious leaders and communities during the pandemic. Their study of a representative sample of twenty-four United Methodist pastors described adaptations that were primarily practical, concerned with new ways of doing ministry or worship.…”
Section: Introductionmentioning
confidence: 99%
“…Their study of a representative sample of twenty-four United Methodist pastors described adaptations that were primarily practical, concerned with new ways of doing ministry or worship. They did note some unsettling of “taken-for-granted understandings of ‘the Church’” and called for further research (Johnston et al 2021 ). While these existing studies helpfully display the spiritual and leadership practices that are emerging in this moment, they do not consider the relationship between the creativity that marks this moment and the religious values and practices that guide leaders’ service in a particular community of faith.…”
Section: Introductionmentioning
confidence: 99%